IMPLEMENTASI DEEP LEARNING PADA PEMBELAJARAN SEJARAH DALAM KURIKULUM NASIONAL SMA - Syakila Zandini; Tsabit Azinar Ahmad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The purpose of the research is to analyze the implementation of the Deep learning approach in history learning at SMA Negeri 4 Semarang, including aspects of lesson planning, classroom implementation, the challenges encountered, and the efforts made to optimize its application. This research employs a qualitative method with a case study approach conducted at SMA Negeri 4 Semarang during the even semester of the 2025/2026 academic year. The research subjects consist of history teachers and students involved in the learning process. Data collection techniques include observation, in-depth interviews, and document analysis. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, with source and technique triangulation applied to ensure the validity of the data. The results show that the implementation of Deep learning has been integrated into lesson planning through learning objectives based on higher order thinking skills, the selection of contextual learning materials, the use of active learning models such as Project-Based Learning, Problem-Based Learning, and Discovery Learning, as well as the application of authentic assessment. The implementation of learning demonstrates active student engagement through discussions, analysis of historical sources, presentations, and project-based activities. However, the implementation of this approach still faces challenges, including differences in students’ critical thinking abilities and teachers’ adaptation to the new approach. Overall, the Deep learning approach at SMA Negeri 4 Semarang contributes to creating history learning that is joyful, meaningful, and mindful for students.This implies that the application of the Deep Learning approach in history learning promotes a more student-centered learning process. Therefore, this research contributes to the body of knowledge on the implementation of Deep Learning in history education at the senior high school level, as well as providing practical contributions for teachers and educational institutions in developing more innovative, contextual, and student-centred learning strategies.